Respiratory health inequality starts early: The impact of social determinants on the aetiology and severity of bronchiolitis in infancy. (27th September 2018) - Foley, David; Best, Elspeth; Reid, Nicholas; Berry, Max (Mary) J
Abstract : Aim: To define the impact of demographics on the incidence, aetiology and clinical course of viral bronchiolitis in infants younger than 2 years of age. Methods: Retrospective case review of all viral bronchiolitis admissions for patients aged younger than 2 years old from January 1 2014 to 31 December 2015 at Wellington Regional Hospital, New Zealand. Demographic data, second‐hand smoke exposure (SHSE) and presence of predisposing conditions were collected, along with outcome data including use of respiratory support and intensive care unit (ICU) admission. This was compared to background rates calculated from regional census data. Results: There were 556 admissions included (11% of paediatric medical admissions); 49% tested positive for respiratory syncytial virus (RSV) (84% tested), and 40% of admissions received positive pressure respiratory support and 10% ICU admission. Admission rates ranged from 9.6 to 77 per 1000/year, with higher rates seen in those from areas of high deprivation. Admission rates by deprivation varied according to aetiology. RSV‐positive admission rates increased from 9.7 per 1000/year to 24.6 per 1000/year in the least to most deprived areas, whereas non‐RSV admissions showed even greater disparity, increasing from 10.1 per 1000/year to 37.5 per 1000/year (both P < 0.0001). Conclusions: This study further reinforces that material deprivation contributes significantly to poor health outcomes that are apparent in infancy. SHSE is a potent risk factor for adverse respiratory outcomes in this patient population. Ongoing efforts to eradicate smoking and reduce material inequality need to continue.